MicroRNA Microarray-Based Identification of Involvement of miR-155 and miR-19a in Development of Oral Lichen Planus (OLP) by Modulating Th1/Th2 Balance via Targeting eNOS and Toll-Like Receptor 2 (TLR2) - Wang, Liang; Wu, Wei; Chen, Jijun; Li, Youhua; Xu, Ming; Cai, Yawei (Medical science monitor, 2018)
BACKGROUND A wide range of microRNAs (miRNAs) have been shown to play a significant role in disease regulation. The objective of this study was to explore the role of miR-155 and miR-19a in the regulation of oral lichen planus (OLP). MATERIAL AND METHODS Microarray assay, real-time PCR, Western blot assay, computational analysis, luciferase assay, ELISA, and immunohistochemistry analysis were carried out to investigate the role of miR-155 and miR-19a in OLP. RESULTS According to microarray assay and real-time PCR results, the expression of miR-155 was most significantly decreased among the 16 candidate miRNAs in the OLP group, whereas the expression of miR-19a was most significantly increased. MiR-155 and miR-19a directly targeted endothelial nitric oxide synthase (eNOS) and TLR2, respectively, since only the cells co-transfected with miR-155/wild-type eNOS 3'UTR or cells co-transfected with miR-19a/wild-type TLR2 3'UTR exhibited decreased luciferase activity. In addition, the expression of TLR2 was highly upregulated in OLP, whereas the expression of eNOS was significantly downregulated. A negative correlation was found between miR-19a and TLR2 mRNA, with a coefficient value of -0.40. Similarly, a negative correlation was found between miR-155 and eNOS mRNA, with a coefficient value of -0.54. A lower level of NO, IL-4, IL-5, and IL-10 was observed in OLP, which was also accompanied by a higher level of TNF-α and IFN-γ. Finally, the upregulation in miR-155 directly decreased the expression of eNOS and further inhibited the production of NO. Downregulation of miR-19a directly increased the expression of TLR2. The inhibition of NO production and the enhancement in TLR2 expression synergistically increased the production of TNF-α and IFN-γ, while decreasing the levels of IL-4, IL-5, and IL-10. CONCLUSIONS In this study, the peripheral blood mononuclear cells (PBMCs) from subjects with or without OLP were collected and their gene expression profiles were compared. It was found that OLP changed the expression profile of miR-155 and miR-19a, which in turn directly affected the production of eNOS and TLR2, respectively. In addition, by synergistically inducing an imbalance between Th1 and Th2, the simultaneous deregulation of miR-155/eNOS and miR-19a/TLR2 was responsible for an elevated risk of OLP.